Understanding the causal influence of major meteorological factors on ground ozone concentrations across China. (1st January 2020) - Chen, Ziyue; Li, Ruiyuan; Chen, Danlu; Zhuang, Yan; Gao, Bingbo; Yang, Lin; Li, Manchun
Abstract: To comprehensively understand meteorological drivers for the soaring ozone pollution across China, an advanced causality analysis model, Convergent Cross Mapping (CCM) was employed to investigate the causal influence of major individual meteorological factors on ground ozone concentrations in 184 monitoring cities. Meteorological influences on O3 _1h and O3 _8h were generally consistent. For most mega cities, temperature, humidity and sunshine duration (SSD) exerted a major influence on ground ozone concentrations in all seasons. Specifically, temperature was the most important meteorological factor for ground ozone concentrations across China. From the perspective of influence direction, temperature, SSD and evaporation exerted a consistent positive influence whilst humidity and precipitation exerted a consistent negative influence on ground ozone concentrations in most cities. On the other hand, the influence direction of wind speed, wind direction and air pressure varied significantly. Based on multi-year comparison, meteorological influences on ground ozone concentrations were generally consistent, and soaring ozone concentrations across China in 2017 could be mainly attributed to the notable change of meteorological conditions in 2017, characterized with rising temperature and SSD and decreasing humidity. Consequently, meteorological means such as wind-corridors and artificial precipitation can be a promising approach for mitigating seasonal and short-term ozone pollution. Highlights: Temperature, humidity and SSD exerted a major influence on ground ozone concentrations. Temperature was the most influential factor for ground ozone concentrations. The influence direction of wind speed, wind direction and air pressure varied significantly. Soaring ozone concentrations in 2017 resulted from favorable meteorological conditions. Meteorological means should be considered for mitigating composite air pollution.